Spheroidisation of hypereutectoid state of nanostructured bainitic steel. (November 2014) - Luo, D.; Peet, M. J.; Ooi, S. W.; Yan, P.; Yin, Z.; Bhadeshia, H. K. D. H.
Abstract : Nanostructured bainite is extremely resistant to severe tempering making it difficult to reduce its hardness sufficiently to allow certain processing before heat treatment into its final state. An attempt is therefore made to introduce the divorced pearlite reaction that relies on the presence of pro-eutectoid cementite in the austenite in order to produce a microstructure containing spheroidal cementite particles simply by continuous cooling from the two phase austenite and cementite field. It is demonstrated that dramatically reduced hardness values can be achieved using this method.